Preparation method and application of composite nanoparticles for promoting osteoarthritis repair protection
By preparing composite nanoparticles, using the combination of dendritic mesoporous silica and bimetallic cluster enzymes, combined with PEG packaging, the problem of long-term retention of drugs in the joint cavity is solved, the drug is sustained release and reactive oxygen scavenging is achieved, and the drug is successfully released and reactive oxygen scavenged, which is promoted. Cartilage repair.
Patent Information
- Application Number
- CN202411586602.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-08
- Publication Date
- 2025-02-11
AI Technical Summary
The prior art is difficult to achieve long-term retention of drugs in the joint cavity, maintain a stable drug concentration, and thus effectively treat osteoarthritis.
The preparation method of composite nanoparticles, including the aminolation of dendritic mesoporous silica nanoparticles and the loading of bimetallic cluster enzymes, combined with the wrapping of PEG, to form nanosized that can sustain the release of drugs and remove reactive oxygen species in a slightly acidic environment. Granules.
It improves the delivery efficiency and biocompatibility of drugs, achieves long-term sustained release of drugs in a slightly acidic environment in the joint cavity, consumes acidic substances and reactive oxygen species, improves the microenvironment of the joint cavity, and thus promotes cartilage repair.
Smart Images

Figure CN119405625A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of medical nanomaterials, and in particular to a preparation method and application of composite nanoparticles for promoting the repair and protection of osteoarthritis. Background Art
[0002] Osteoarthritis is a prevalent joint disorder that affects millions of people worldwide. It is a degenerative disease characterized by the gradual degradation of the protective cartilage that cushions the joints. Subsequently, the bones within the joint rub directly against each other, leading to problems primarily in the hands, hips, and knees. This causes discomfort, swelling, and stiffness. The onset of symptomatic osteoarthritis of the hands, hips, and knees follows a steep trajectory around age 50, leveling off after age 70. Progressive degeneration of the articular cartilage, thickening of the subchondral bone, and the formation of osteophytes define osteoarthritis, which cumulatively lead to impaired joint mobility and decreased function.
[0003] Therefore, nanoparticles that can achieve intra-articular drug delivery have become a research hotspot. This treatment strategy often requires the drug to remain in the joint cavity for a long time to maintain a stable drug concentration. Summary of the invention
[0004] 1. Technical issues to be solved The purpose of the present invention is to solve the problem in the prior art that drugs need to be retained in the joint cavity for a long time to maintain a stable drug concentration, and to propose a preparation method and application of composite nanoparticles that promote osteoarthritis repair and protection.
[0005] 2. Technical solution In order to achieve the above object, the present invention adopts the following technical solutions: A method for preparing composite nanoparticles for promoting osteoarthritis repair and protection comprises the following steps: Step 1: Preparation of dendritic mesoporous silica nanoparticles DMSNs; Step 2: Preparation of aminated dendritic mesoporous silica DMSNs-NH2; Step 3: Single-atom replacement of Au in bimetallic cluster enzyme 24 Preparation of Cu1 clusterzymes; Step 4: Prepare the Au 24 Cu1 is dispersed in deionized water, and the DMSNs-NH2 prepared in step 2 is dispersed in the above solution, and stirred to obtain solution 1; Step 5: Dissolve the amino-PEG (NH2-PEG-NH2) in solution 1 and wash with deionized water to obtain a nanoparticle complex.
[0006] Preferably, the step 1 is specifically: Step 1.1: DMSNs were synthesized by a one-pot method using surfactants cetyltrimethylammonium bromide and sodium salicylate as structure-directing agents, n-ethyl tetrasilicate as a silica source, and triethanolamine as a catalyst; Step 1.2: First, add 0.068 g of triethanolamine to 25 ml of water and stir in an 80°C oil bath for 0.5 hour. Then, add 380 mg of hexadecyltrimethylammonium bromide and 168 mg of sodium salicylate to the above solution and continue stirring for 2 hours. Step 1.3: Then 4 ml of TEOS was added and gently stirred at 300 rpm for 3 h. The product was collected by high-speed centrifugation and washed with ethanol several times to remove the residual reactants. Then, concentrated hydrochloric acid and methanol solution were mixed with the collected product at 60.0 °C for 6 h, three times in total, to remove the template. The final product was dried in vacuum at room temperature overnight.
[0007] Preferably, the step 2 is specifically: Step 2.1: Add 0.50 g DMSNs and 0.5 ml (3-aminopropyl)triethoxysilane to 100 ml toluene, stir in an oil bath at 80 °C, and reflux for 4 h; Step 2.2: Collect the product and wash it with toluene several times.
[0008] Preferably, the step 3 is specifically: Step 3.1: Prepare 20 mM chloroauric acid and take 0.24 mL, mix it with 0.01 mL copper nitrate, add 2 mL of 5 mM MPA, dilute to 2.35 mL and stir at room temperature for 5 minutes, then add 0.3 mL of 1 M sodium hydroxide solution; Step 3.2: Meanwhile, 43 mg of sodium borohydride was dissolved in 10 ml of 0.2 M NaOH solution, added to the system, and mixed for reaction for 3 hours. The final reaction solution was aged at 4°C for 12 hours. The entire reaction was carried out in the dark. In order to collect the purified product, ultrafiltration was used to remove smaller organic ligands and larger clusters, and the purified product was lyophilized for further testing and application.
[0009] Preferably, in step 4, the concentration of DMSNs is 2.5 ng / μl, and the stirring ratio of DMSNs to the dual metal cluster enzyme is 1:1.
[0010] Preferably, the amount of NH2-PEG-NH2 used in step 5 is 10 mg; the two are stirred at 4° C. for 12 hours to allow the NH2-PEG-NH2 to be completely dissolved in deionized water and fully mixed with the material.
[0011] The present invention also provides a composite nanoparticle, which is prepared by the above preparation method.
[0012] The present invention also proposes the application of the composite nanoparticles in osteoarthritis treatment and cartilage protection.
[0013] 3. Beneficial effects Compared with the prior art, the advantages of the present invention are: (1) In the present invention, the outer surface of the prepared CDP nanoparticles is coated with NH2-PEG-NH2, which on the one hand enhances the biocompatibility and dispersibility of the nanoparticles, and on the other hand enhances the phagocytic ability of cells for drugs, thereby improving the drug delivery efficiency.
[0014] (2) In the present invention, CDP can achieve sustained drug release and reactive oxygen scavenging capabilities in a slightly acidic environment in the joint cavity. At the same time, it can consume acidic substances and reactive oxygen to improve the microenvironment of the joint cavity, thereby promoting cartilage repair. BRIEF DESCRIPTION OF THE DRAWINGS
[0015] Figure 1 AG are transmission electron microscope images, scanning electron microscope images, energy spectrum images, BET aperture analysis, Fourier transform infrared spectrum, and Zeta potential analysis of Example 1 of the present invention and Comparative Example 1, respectively. Scale bars in the figures: A is 200 nm, and B is 200 nm; Figure 2 AJ are respectively the CDP preparation ratio verification diagram and the surface view comparison diagram of Example 2 and Example 3 of the present invention; the degradation rate comparison diagram of Comparative Example 2, and the cluster enzyme activity measurement diagram therein; Figure 3 The AIs are respectively the surface observation comparison diagram of Example 2, Example 3 and Comparative Example 3 of the present invention, the XPS comparison diagram, the near infrared spectrum diagram before and after adding hydrogen peroxide, the EPR measurement diagram of the antioxidant capacity within 10 minutes and the theoretical calculation of the antioxidant capacity; Figure 4 AF are respectively the CCK8 cell viability curve of chondrocytes used in cell experiments of the present invention, dead / live staining fluorescence image, antioxidant capacity and mitochondrial change cell image, chondrocyte oxidative stress level flow cytometric image, WB protein level change, and Alizarin blue cartilage matrix staining image. Scale bars in the figures: C are 15 μm and 40 μm respectively; Figure 5 AF are respectively the RNA-seq analysis results for in vitro experiments of the present invention, the flow cytometry results of chondrocyte apoptosis, the level of changes in Hippo pathway-related proteins, and the comparison of the effects of P65 entering the nucleus. Scale bars in the figures: F is 50 μm; Figure 6 The AIs are respectively a flow chart of establishing the experimental model for in vivo experiments of the present invention, a magnetic resonance imaging image, a joint surface observation image, a micro-CT imaging image, a safranin fast green section staining image and a structure scoring quantification image; Figure 7 AE are respectively the immunofluorescence staining diagram and the quantitative statistical diagram used for in vivo experiments of the present invention. DETAILED DESCRIPTION
[0016] The technical solutions in the embodiments of the present invention will be described clearly and completely below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments.
[0017] A method for preparing composite nanoparticles for promoting osteoarthritis repair and protection comprises the following steps: Step 1: Preparation of dendritic mesoporous silica nanoparticles DMSNs; Step 2: Preparation of aminated dendritic mesoporous silica DMSNs-NH2; Step 3: Single-atom replacement of Au in bimetallic cluster enzyme 24 Preparation of Cu1 clusterzymes; Step 4: Prepare the Au 24 Cu1 was dispersed in deionized water, and the DMSNs-NH2 prepared in step 2 was dispersed in the above solution and stirred to obtain solution 1, in which the concentration of DMSNs was 2.5 ng / μl, and the stirring ratio with the dual metal cluster enzyme was 1:1; Step 5: Dissolve the amino PEG (NH2-PEG-NH2) in solution 1, and obtain the nanoparticle complex by washing with deionized water. The amount of NH2-PEG-NH2 used is 10 mg. Stir the two at 4°C for 12 hours to completely dissolve the NH2-PEG-NH2 in the deionized water and fully mix with the material.
[0018] In the present invention, the outer surface of the prepared CDP nanoparticles is coated with NH2-PEG-NH2, which on the one hand enhances the biocompatibility and dispersibility of the nanoparticles, and on the other hand enhances the phagocytic ability of cells to drugs, thereby improving the delivery efficiency of drugs.
[0019] In the present invention, CDP can achieve sustained drug release and active oxygen scavenging capabilities in a slightly acidic environment in the joint cavity. At the same time, it can consume acidic substances and active oxygen to improve the microenvironment of the joint cavity, thereby promoting cartilage repair.
[0020] Embodiment 1: In this example, DMSNs were synthesized by a one-pot method using surfactants cetyltrimethylammonium bromide and sodium salicylate as structure-directing agents, ethyl tetrasilicate as a silica source, and triethanolamine as a catalyst. First, 0.068 g of triethanolamine was added to 25 ml of water and stirred in an 80°C oil bath for 0.5 hours. Then, 380 mg of cetyltrimethylammonium bromide and 168 mg of sodium salicylate were added to the above solution and stirred for 2 hours. In this example, 4 ml of TEOS was then added and stirred gently (~ 300 rpm) for 3 hours. The product was collected by high-speed centrifugation and washed with ethanol several times to remove residual reactants. Then, concentrated hydrochloric acid and methanol solution were mixed with the collected product at 60.0°C for 6 hours, three times in total, to remove the template. The final product was dried in vacuo at room temperature overnight. 0.50 g of DMSNs and 0.5 ml of (3-aminopropyl)triethoxysilane were added to 100 ml of toluene, stirred in an oil bath at 80°C, and refluxed for 4 hours. The product was collected, washed several times with toluene, and freeze-dried for storage.
[0021] Embodiment 2: In this embodiment, 20mM chloroauric acid was prepared, and 0.24mL was taken, mixed with 0.01mL copper nitrate, 2mL of 5mM MPA was added, the volume was fixed to 2.35mL and stirred at room temperature for 5 minutes, and then 0.3ml of 1M sodium hydroxide solution was added. At the same time, 43mg of sodium borohydride was dissolved in 10ml of 0.2M NaOH solution, added to the system, mixed for 3 hours, and the final reaction solution was aged at 4°C for 12 hours, and the entire reaction was carried out in the dark. In order to collect the purified product, we used ultrafiltration to remove smaller organic ligands and larger clusters, and lyophilized to obtain the purified product for further testing and application.
[0022] Embodiment 3: In this example, CD was prepared by adding 5 ml of DMSNs-NH2 with a concentration of 2.5 ng / μl to the double metal cluster enzyme at a stirring ratio of 1:1 with the double metal cluster enzyme, and stirring was carried out at 4°C overnight.
[0023] In this example, CDP was prepared by dissolving 10 mg NH2-PEG-NH2 in 5 mL (1), stirring at 4°C overnight, and washing three times with deionized water to obtain CDP.
[0024] Comparative Example 1: DMSNs were synthesized by a one-pot method using surfactants cetyltrimethylammonium bromide and sodium salicylate as structure-directing agents, n-ethyl tetrasilicate as a silica source, and triethanolamine as a catalyst. First, 0.068 g of triethanolamine was added to 25 ml of water and stirred in an oil bath at 80 °C for 0.5 h. Then, 380 mg of cetyltrimethylammonium bromide and 168 mg of sodium salicylate were added to the above solution and stirred for 2 h. Then, 4 ml of TEOS was added and stirred gently (~ 300 rpm) for 3 h. The product was collected by high-speed centrifugation and washed with ethanol several times to remove residual reactants. Then, concentrated hydrochloric acid and methanol solution were mixed with the collected product at 60.0 °C for 6 h, for a total of three times, to remove the template. The final product was dried overnight in vacuum at room temperature.
[0025] like Figure 1 As shown, the prepared DMSNs, DMSNs-NH2, CD and CDP were characterized. Figure A and Figure B show the SEM, TEM and element distribution images of CC and CCP respectively; Figure C and Figure D show the pore size distribution and size of DMSNs, DMSNs-NH2, CD and CDP, indicating that PEG was successfully encapsulated on CDP and the cluster enzyme was loaded into the mesopores; Figure E shows the change of infrared light absorption peak after amination of nanoparticles; Figure F is the change of particle size of DMSNs, DMSNs-NH2, CD and CDP, indicating that PEG modification and cluster enzyme loading have no effect on particle size; Figure G is the change of zeta potential of DMSNs, DMSNs-NH2, CD and CDP, indicating that CDP was successfully synthesized and the regulation of nanoparticle potential was achieved.
[0026] Comparative Example 2: After the synthesis of clustering enzymes with DMSNs-NH2, the supernatant and precipitate after centrifugation were digested with digestion solution (3% H2O2: HNO3 = 3:1) for 72h. Then the concentration of gold was measured. For the release rate, the precipitate was stored in a centrifuge tube with normal PBS (pH =7.4) or acidic PBS (pH =6.5) at 37°C, and the supernatant was extracted every other day and digested and measured.
[0027] The same concentration of DMSNs-NH2 was added to neutral (pH = 7.4) or slightly acidic (pH = 6.5) PBS, shaken at a constant speed on a shaker, and liquid samples were extracted regularly and TEM photos were taken.
[0028] like Figure 2As shown, we verified the basic properties of CDP after in vitro loading. Figures A and B show the changes in the antioxidant capacity of CDP under different component ratios, from which we obtained a reasonable synthetic concentration; Figure C is a surface appearance comparison between the components. Figures D and E show the difference in the degradation and release rate of CDP in a simulated slightly acidic environment in vitro and in a neutral environment. It can be seen that in a neutral environment, CDP degrades rapidly, indicating that it will be quickly cleared in a normal joint environment, while in a slightly acidic environment it can be retained for a long time and play a sustained release function. Figures F and G are a comparison of the antioxidant capacity of CDP extracted under the two environments. It can be seen that under the protection of the CDP shell, there is no significant difference in the antioxidant capacity of the two. Figures H, I and J are quantitative comparisons of their antioxidant capacity.
[0029] Comparative Example 3: Total antioxidant capacity test (ABTS rapid method): The total antioxidant capacity (T-AOC) of clusterin and control (trolox and anthocyanin) was determined by the rapid ABTS method using T-AOC Assay Kit (S0121, Beyotime). Please refer to the specification for specific sampling methods. The antioxidant capacity was evaluated by measuring its absorbance at 414 nm.
[0030] like Figure 3 As shown, the antioxidant capacity of the prepared CDP was characterized and compared with DMSNs-NH2 and hydrogen peroxide. Figure A shows the bubbles generated in hydrogen peroxide. Figures B and C are XPS characterizations of the cluster enzyme before and after storage in hydrogen peroxide for 3 weeks. It can be seen that while the cluster enzyme exerts its antioxidant capacity in hydrogen peroxide, its own properties have not changed, proving the nature of its enzyme. Figure D is a comparison of the infrared spectra of the two, and there is no change. Figures E and F are EPR comparisons of CDP and hydrogen peroxide after adding hydrogen peroxide, proving that it has strong antioxidant properties. Figures G, H and I are theoretical calculations of the process.
[0031] Application Example 1: Verification of the protective effect of nanoparticle complexes on chondrocytes in vitro: Co-culture CDP with chondrocytes, such as Figure 4 A and Figure 4 As shown in B, the cells survived well and the death rate did not exceed 5%, so it can be considered that CDP has good biosafety. Figure 4 C was stimulated by adding hydrogen peroxide to chondrocytes, and then its antioxidant capacity was verified by supplementing CDP, which proved that it can relieve the oxidative stress of chondrocytes by removing reactive oxygen. Figure 4 D is a supplement to Figure C, which also proves that CDP can rescue chondrocytes through flow cytometry. Figure 4E is the characterization of common proteins of chondrocytes by WB, indicating that the addition of CDP can increase the production of cartilage proteins. Figure 4 F is the comparison of the changes in cartilage matrix components through Arixin blue staining, which shows that CDP promotes the formation of cartilage matrix.
[0032] Application Example 2: Verification of the protective mechanism of nanoparticle complexes on chondrocytes in vitro: We studied the mechanism of action of CDP on cartilage in vitro by RNA-seq. Figure 5 A, Figure 5 B and Figure 5 C is part of the results of RNA-seq, from which we determined that CDP's effect on the Hippo pathway regulated cartilage formation. Figure 5 D is the observation result of flow cytometry on the reduction of apoptosis of chondrocytes under the influence of CDP in 1 mM hydrogen peroxide environment, which proves its effect of reducing cell apoptosis. Figure 5 E is the quantification of Hippo pathway-related proteins and phosphorylated proteins. Figure 5 F is the fluorescence localization of the reduced nuclear entry of downstream P65, which proves the regulatory effect of CDP on the Hippo pathway.
[0033] Application Example 3: Verification of the effect of nanoparticle complex on joint protection in rabbit arthritis model: Male New Zealand rabbits (n = 50, 4.50 ± 0.2 kg) were surgically established with ACLT to establish an OA model. Under aseptic conditions, the patella was dislocated laterally and flexed to its maximum extent through a medial parapatellar approach to visualize and identify the anterior cruciate ligament, which was then transected using a sterile No. 11 blade. The knee joint and skin incision were irrigated with sterile saline and closed with 4-0 nylon sutures. Appropriate transection of the ACL was confirmed by observation of cruciate ligament laxity by anterior drawer and Lachman tests. Sham-operated animals underwent the same surgery except for transection of the ligament. To obtain the preventive ability of CDP, 0.2 ml of CDP (n = 6), clusterase alone (n = 6), or DP alone (n = 6) were injected intra-articularly after 4, 6, or an additional 4-week delay to simulate severe OA.
[0034] like Figure 6 B and Figure 6 As shown in Figure C, we observed the thickness of the articular cartilage layer in each group by magnetic resonance imaging, proving the protective effect of clusterin and CDP on cartilage. Figure 6 As shown in D, we observed the extent of subchondral bone destruction by micro-CT, demonstrating the destructive effect of the arthritis model on subchondral bone and the protective effect of CDP on it. Figure 6 E to Figure 6 IThe bone articular surface of each group was characterized and quantified by safranin fast green staining, demonstrating the integrity of the articular cartilage structure in the CDP group. Figure 7 A to Figure 7 E was stained by immunofluorescence staining of YAP1 and Collagen II, which play a protective role in cartilage, and Aggrecan and MMP13, which play a destructive role. The increase of the former two and the decrease of the latter two proved the protective effect of CDP on cartilage.
[0035] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A method for preparing composite nanoparticles for promoting osteoarthritis repair and protection, comprising the following steps: Step 1: Preparation of dendritic mesoporous silica nanoparticles DMSNs; Step 2: Preparation of aminated dendritic mesoporous silica DMSNs-NH2; Step 3: Single-atom replacement of Au in bimetallic cluster enzyme 24 Preparation of Cu1 clusterzymes; Step 4: Prepare the Au 24 Cu1 is dispersed in deionized water, and the DMSNs-NH2 prepared in step 2 is dispersed in the above solution, and stirred to obtain solution 1; Step 5: Dissolve the amino-PEG (NH2-PEG-NH2) in solution 1 and wash with deionized water to obtain a nanoparticle complex.
2. The method for preparing composite nanoparticles for promoting repair and protection of osteoarthritis according to claim 1, characterized in that: The step 1 is specifically as follows: Step 1.1: DMSNs were synthesized by a one-pot method using surfactants cetyltrimethylammonium bromide and sodium salicylate as structure-directing agents, n-ethyl tetrasilicate as a silica source, and triethanolamine as a catalyst; Step 1.2: First, add 0.068 g of triethanolamine to 25 ml of water and stir in an 80°C oil bath for 0.5 hour. Then, add 380 mg of hexadecyltrimethylammonium bromide and 168 mg of sodium salicylate to the above solution and continue stirring for 2 hours. Step 1.3: Then 4 ml of TEOS was added and gently stirred at 300 rpm for 3 h. The product was collected by high-speed centrifugation and washed with ethanol several times to remove residual reactants. Then, concentrated hydrochloric acid and methanol solution were mixed with the collected product at 60.0 °C for 6 h, three times in total, to remove the template. The final product was dried in vacuum at room temperature overnight.
3. The method for preparing composite nanoparticles for promoting osteoarthritis repair and protection according to claim 1, characterized in that: The step 2 is specifically as follows: Step 2.1: Add 0.50 g DMSNs and 0.5 ml (3-aminopropyl)triethoxysilane to 100 ml toluene, stir in an oil bath at 80 °C, and reflux for 4 h; Step 2.2: Collect the product and wash it with toluene several times.
4. The method for preparing composite nanoparticles for promoting repair and protection of osteoarthritis according to claim 1, characterized in that: The step 3 is specifically as follows: Step 3.1: Prepare 20 mM chloroauric acid and take 0.24 mL, mix it with 0.01 mL copper nitrate, add 2 mL of 5 mM MPA, dilute to 2.35 mL and stir at room temperature for 5 minutes, then add 0.3 mL of 1 M sodium hydroxide solution; Step 3.2: Meanwhile, 43 mg of sodium borohydride was dissolved in 10 ml of 0.2 M NaOH solution, added to the system, and mixed for reaction for 3 hours. The final reaction solution was aged at 4°C for 12 hours. The entire reaction was carried out in the dark. In order to collect the purified product, ultrafiltration was used to remove smaller organic ligands and larger clusters, and the purified product was lyophilized for further testing and application.
5. The method for preparing composite nanoparticles for promoting osteoarthritis repair and protection according to claim 1, characterized in that: In step 4, the concentration of DMSNs is 2.5 ng / μl, and the stirring ratio of DMSNs to the dual metal cluster enzyme is 1:
1.
6. The method for preparing composite nanoparticles for promoting repair and protection of osteoarthritis according to claim 1, characterized in that: The amount of NH2-PEG-NH2 used in step 5 is 10 mg; the two are stirred at 4° C. for 12 hours to allow the NH2-PEG-NH2 to be completely dissolved in deionized water and fully mixed with the materials.
7. A composite nanoparticle, characterized in that: The invention is prepared by the preparation method according to any one of claims 1 to 6.
8. The use of the composite nanoparticles according to claim 7, characterized in that: Application in osteoarthritis treatment and cartilage protection.